A Study of School Library Resources for Reading Interests of Secondary School Students in Ogun State, Nigeria - Ajegbomogun, Fredrick Olatunji; Ajegbomogun, Veronica Olufunmilola (MiddleBelt Journal of Library and Information Science, 2015)
This study assessed school library resources as a prequisite for reading interest of secondary school students in Abeokuta South Local Government Area of Ogun State, Abeokuta. A structured questionnaire was designed to elicit the desired information. 400 students were sampled, from Egba Comprehensive High School, Asero High School, Reverend Kuti Memorial Grammar School and Abeokuta Grammar School. The data collected were analysed using simple descriptive statistics, frequency tables and percentages. Report of the findings indicates the average age range of the respondents which falls between 13-17 years. It also showed that senior secondary school three (SS3) forms the majority of the study. Finding indicates that majority of the respondents found library resources useful for their studies and can access library resources easily. The finding also reveals that students gave top priority to books over other resources in their libraries. The study also reveals that the majority of the respondents indicated that library resources have great impact on their reading interest. It is therefore recommended that qualified librarians should be employed to manage the school libraries in order to provide services that will sustain reading interest of the students